Pelaksanaan Pembinaan Narapidana Pada Lembaga Pemasyarakatan Super Maximum Security Di Lembaga Pemasyakatan Kelas I Batu Nusakambangan - Mokhamad Hadi Syafa’at; Arif Awaluddin; Ikama Dewi Setia Triana; Muhammad Yusril Irza (Wijayakusuma Law Review, 2025)
Correctional Institutions are places designed to accommodate and nurture inmates. Prisoner coaching is carried out through a correctional revitalization program. The goal of inmate development that needs to be achieved through the revitalization program is to improve the quality of the inmate coaching function in encouraging behavior change and reducing the level of inmate risk through implementing intervention programs for inmates in stages with accountable assessments. Coaching is expected to change inmates into better individuals and prevent them from repeating the same crimes. However, reality shows that there are still many inmates who, after serving their sentences, return to crime and become recidivists. Based on the concept of coaching in the form of Correctional Revitalization, the prison classification is differentiated based on the characteristics of the inmate's risk level, namely Super Maximum Security, Maximum Security, Medium Security, and Minimum Security Prisons. This study examines how to implement inmate coaching in the Super Maximum Security  Prison in Batu Nusakambangan Class I Prison and identifies obstacles or obstacles faced during the process, especially in the Batu Nusakambangan Class I Correctional Institution. The purpose of this study is to understand the appropriateness of the implementation of inmate coaching and identify existing obstacles. The method of approach to this research uses a juridical-empirical approach, the data used is primary data through interviews with sources and secondary data as supporting data in the form of legal materials, analyzed thoroughly with the specifications of descriptive research analysis. All results that have been collected will be compiled in the form of descriptions to facilitate data implementation and understanding of analysis. From the research results, it can be concluded that the implementation of Prisoner Development in the Super Maximum Security Prison runs by the applicable Regulation of the Minister of Law and Human Rights Number 35 of 2018.